2015
DOI: 10.1002/pon.3879
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of oncologist-issued referrals for psycho-oncology services: what we learned from the electronic voluntary screening and referral system for depression (eVSRS-D)

Abstract: The eVSRS-D cannot definitively diagnose major depression but may efficiently self-select a population with significant depression symptoms. The patients' willingness to engage the POS most strongly predicted the actual referrals. Oncologist reviews of screening reports may not result in further depression severity-specific referrals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
4
10
0
Order By: Relevance
“…Consistent with other research (Lee et al, 2016), in our study a higher level of distress was associated with higher odds of being offered a referral. However, analyses considering the type Notes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with other research (Lee et al, 2016), in our study a higher level of distress was associated with higher odds of being offered a referral. However, analyses considering the type Notes.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other research (Lee et al., ), in our study a higher level of distress was associated with higher odds of being offered a referral. However, analyses considering the type of referral revealed that distress did not significantly relate to all offers, although it was significant for offers of practical support.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, severity of depression was not found to be related to physician referral or real referral with psycho‐oncology services by univariate or multivariate analyses. In a previous study, it was reported that severity of depression was associated with physician referral to psycho‐oncology services but not to real referral . In another study, oncologist‐assessed depression was found to be mainly dependent on patient medical correlates, regardless of the presence of depression or its severity, and these findings were considered to reflect the inability of oncologists to diagnose depression …”
Section: Discussionmentioning
confidence: 98%
“…Lastly, whilst this study has not quantified the efficacy of the CPSSS in alleviating patient psychological distress, the service is a positive addition, particularly given the highly distressing nature of lung cancer, the poor prognosis and stigma associated with the disease. However, with only 6.5% of lung cancer patients in the Waikato region being referred during the study period, the number of patients being referred is lower than reported in other countries and may represent an unmet need in NZ, particularly for Māori. Thus, it is imperative that psychosocial support services continue to be made accessible (and be appropriately delivered to) both Māori and non‐Māori lung cancer patients within the Waikato region of NZ.…”
Section: Discussionmentioning
confidence: 99%